Sagot :
Answer:
2x²-5x+4
Step-by-step explanation:
(5ײ-8×+6)-(3ײ-3×+2)
5x²-3x²=2x²
(-8x)-(-3x)
(-8x)+(3x)
=-5x
6-2=4
=2x²-5x+4
PAVOTE HEART AND BRAINLIEST!
I research it on Guatmath
brainlest me if it is right
thank you
![View image Rowenadelosreyes214](https://ph-static.z-dn.net/files/d1f/24215c202482af10347a8ffb91ebb148.jpg)
![View image Rowenadelosreyes214](https://ph-static.z-dn.net/files/dba/2fdb68d850426a98fb1c99bfe371f05a.jpg)
Answer:
2x²-5x+4
Step-by-step explanation:
(5ײ-8×+6)-(3ײ-3×+2)
5x²-3x²=2x²
(-8x)-(-3x)
(-8x)+(3x)
=-5x
6-2=4
=2x²-5x+4
PAVOTE HEART AND BRAINLIEST!
I research it on Guatmath
brainlest me if it is right
thank you